Effects of Liquidity and Solvency on Stock Investment Returns in PT Telkom Indonesia Tbk for the 2014-2025 Period - Nurwita; Noryani; Lisdawati (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
This study analyzes the effects of liquidity and solvency on stock investment returns in PT Telkom Indonesia Tbk for the 2014-2025 period. A quantitative design is applied using secondary data from the company’s annual financial statements and year-end stock closing prices. Liquidity is measured by the current ratio, while solvency is measured by the debt to equity ratio. Stock investment return is calculated from yearly stock price changes. The data are tested through multiple linear regression with SPSS version 26. The findings show that liquidity and solvency have no significant effect on stock investment returns, either individually or jointly. The coefficient of determination reaches 45.2%, meaning that both financial ratios explain less than half of the variation in stock investment returns. The remaining 54.8% is linked to other factors outside the model. This result suggests that a healthy liquidity or solvency position does not automatically lead to higher stock returns. Investors need to compare these ratios with profitability, dividend policy, interest rates, market sentiment, and industry conditions before making investment decisions.